2005
DOI: 10.1007/s00428-005-1228-0
|View full text |Cite
|
Sign up to set email alerts
|

Augmented expression of metallothionein and glutathione S-transferase pi as unfavourable prognostic factors in cisplatin-treated ovarian cancer patients

Abstract: Resistance to cis- or carboplatin represents the principal cause of therapeutic failures in ovarian carcinoma. The phenomenon of resistance to platinum-based drugs is partly related to expression of metallothionein (MT) and of glutathione S-transferase pi (GST-pi), but opinion on the subject is discordant. Documentation of a negative predictive effect of MT and GST-pi expression for the therapy employing platinum-based drugs would permit to select resistant cases in which other therapeutic approaches could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
1
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 22 publications
5
63
1
6
Order By: Relevance
“…For example, GST can acylate and inactivate cisplatin (16,17). The current study demonstrated that GST levels significantly increased in HepG2/DDP cells and significantly decreased subsequent to WEE1 silencing, suggesting that GST was also involved in WEE1-mediated drug resistance to cisplatin.…”
Section: Discussionsupporting
confidence: 50%
“…For example, GST can acylate and inactivate cisplatin (16,17). The current study demonstrated that GST levels significantly increased in HepG2/DDP cells and significantly decreased subsequent to WEE1 silencing, suggesting that GST was also involved in WEE1-mediated drug resistance to cisplatin.…”
Section: Discussionsupporting
confidence: 50%
“…GST-π is a member of the GST family that is able to catalyze the binding of hydrophobic and A B electrophilic compounds, including cisplatin, with reduced glutathione, causing the former to lose toxicity (28). This represents an additional mechanism of tumor cell resistance to chemotherapeutic drugs (29,30). The current study revealed that the GST-π expression level decreased significantly in A549/dox cells following miR-155 silencing, indicating the involvement of GST-π in miR-155-mediated drug resistance.…”
Section: Discussionmentioning
confidence: 67%
“…In the last decade, several reports disclosed MT overexpression as a useful prognostic factor for tumour progression and drug resistance in a variety of cancers such as ovarian cancer (Surowiak et al, 2005), renal cell carcinoma (Mitropoulos et al, 2005), breast cancer (Jin et al, 2004), non-small-cell lung carcinomas (Dziegiel et al, 2004), acute lymphoblastic leukaemia (Sauerbrey et al, 1994), pancreatic carcinoma (Ohshio et al, 1996) or carcinoma of the gallbladder (Shukla et al, 1998). Similar results could be found in smaller retrospective studies in melanoma and nonmelanoma skin cancers (Zelger et al, 1993(Zelger et al, , 1994Rossen et al, 1997;Goldmann et al, 1998;Sugita et al, 2001).…”
mentioning
confidence: 99%